2000
DOI: 10.1177/0010414000033001004
|View full text |Cite
|
Sign up to set email alerts
|

Membership Has Its Privileges

Abstract: This article compares the relative importance of political capital (in the form of membership in the Chinese Communist Party) and human capital (in the form of higher education) in urban China. Survey data from urban China strongly support two key elements of the intellectual New Class theory: intellectuals will have privileged access into the party, and the importance of education relative to political reliability will increase over time. The data also show how political capital and human capital are converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(15 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…Previous studies have indicated that being a member of the communist party in China is positively correlated with beneficial social and economic outcomes (e.g., better paying jobs, higher household income, and wealth accumulation; Dickson & Rublee, 2000;Huang et al, 2013;Li, Liu, Zhang, & Ma 2007;Meng, 2007). Our study extended the literature by showing that communist party membership not only benefits household income and wealth but also affects the use of formal credit, a valuable resource that is restrained in the Chinese financial market.…”
Section: Low Prevalence Of Formal Credit Usesupporting
confidence: 70%
“…Previous studies have indicated that being a member of the communist party in China is positively correlated with beneficial social and economic outcomes (e.g., better paying jobs, higher household income, and wealth accumulation; Dickson & Rublee, 2000;Huang et al, 2013;Li, Liu, Zhang, & Ma 2007;Meng, 2007). Our study extended the literature by showing that communist party membership not only benefits household income and wealth but also affects the use of formal credit, a valuable resource that is restrained in the Chinese financial market.…”
Section: Low Prevalence Of Formal Credit Usesupporting
confidence: 70%
“…Such mediation can be the result of peer groups in education (Harris, 1995), or education affecting individuals’ social network centrality (Nie et al, 1996). Indeed, many student groups have been ardent supporters of authoritarian rulers (Glaeser et al, 2007); in one-party states, party membership provides access to social networks used to gain access to certain jobs (Dickson and Rublee, 2000); and some form of higher education is all but necessary to gain access to positions of political influence in non-democracies (Kryshtanovskaya and White, 1996). As such, a conditional effect of education would be expected given an indirect effect via social networks as well.…”
Section: Education and Support For Democracymentioning
confidence: 99%
“…Menachem Hofnung (1996) shows one direct consequence of the adoption of primaries in Israel: the rapid growth in party membership. Legitimacy is gained through mass membership (Dickson and Rublee, 2000; Scarrow, 2000, p. 84) and members secure stable support within marginal groups (Geser, 1999, p. 13) or constituencies.…”
Section: The Benefits Of Primariesmentioning
confidence: 99%